Never-Fail Blake - Stringer, Arthur, 1874-1950 (Salt Lake City, UT : Project Gutenberg, 2006)
"Never-Fail Blake" by Arthur Stringer is a detective novel written in the early 20th century. The book centers around James Blake, a seasoned Second Deputy Commissioner known for his dogged determination and instinctual abilities as a detective, as he navigates the murky waters of crime and deception in pursuit of a notorious conman named Connie Binhart. The narrative explores themes of law, morality, and the complexities of human relationships in the backdrop of a criminal world. The opening of the novel introduces Blake and a pivotal female character, Elsie Verriner, who presents a blend of beauty and danger, as they engage in a cat-and-mouse dialogue in his office. Blake reflects on their tumultuous past encounters and her previous involvement in criminal activities, revealing the tension and unresolved feelings between them. As their conversation unfolds, Blake confronts the reality of his investigation into Binhart's whereabouts, and when Elsie reluctantly offers information, it sets the stage for the complicated interplay of personal and professional motives. The narrative establishes Blake as a reluctant yet undeniable romantic figure, while also hinting at the challenges and betrayals he may face as he seeks to uphold the law. (This is an automatically generated summary.)
Release date is 2006-06-23
E-text pepared by Al Haines
Keywords: Detective and mystery stories; Canadian fiction